DEVELOPMENT OF SUSTAINABLE INTERLOCKING PAVEMENT BLOCK (SIPB) USING HIGH-DENSITY POLYETHYLENE (HDPE) AND RECYCLED ASPHALT PAVEMENT (RAP) - Tuan Noor Hasanah Tuan Ismail, Tuan Noor Hasanah Tuan Ismail; Muhammad Fariz Abdul Wahab, Muhammad Fariz Abdul Wahab; Suraya Hani Adnan, Suraya Hani Adnan; Andri Kusbiantor, Andri Kusbiantor; Nik Normunira Mat Hassan, Nik Normunira Mat Hassan; Faezah Yahya, Faezah Yahya; Harina Md Amin, Harina Md Amin; Wan Amizah Wan Jusoh, Wan Amizah Wan Jusoh (2023)
Interlocking pavement block (IPB) has been extensively used in many countries for many years as a specialized problem-solving technique that provides pavement in areas where conventional types of construction are less durable due to many operational and environmental constraints. In developing IPB, cement, sand, and aggregates are frequently utilised, which at present these resources are limited and leading to many environmental impacts. This study attempts to examine the potential of sustainable IPB by substituting Portland cement with HighDensity Polyethylene (HDPE) and aggregates with Recycled Asphalt Pavement (RAP). The alternative IPB were prepared in different HDPE and RAP blends, namely 1:3, 1:4, 1:5 and 1:6. The potential of IPB was evaluated through three series of tests: density test, water absorption test, and compression test. The findings of this study showed that the highest compressive strength of 7.65 MPa was achieved by HDPE and RAP blending proportion of 1:3 (1H3R). Furthermore, the widespread use of HDPE plastic waste and RAP as new alternative building materials would help reduce the quantity of plastic waste and RAP in landfills while promoting green technology